Evaluation of the implementation of Indonesia Pintar program in vocational school - Hamdi, Syukrul; Setiawan, Risky; Musyadad, Faridl (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The study aims to evaluate a program of channeling educational fund, Program Indonesia Pintar (PIP), for vocational school (sekolah menengah kejuruan or SMK). This research was evaluation research using mix method approach. The evaluation model used was the CIPP model covering context, input, process, and product. The respondents of the study were 702 principals, 125 student’s parents, and 15853 students of the SMKs spreading across 29 out of 34 provinces in Indonesia. Data collection techniques used were analysis, survey, interview, observation, and study documentation. The instruments used were analysis sheets, questionnaires, interview guidelines, observation sheets, and the list of related documents. Data analysis techniques used were quantitative descriptive and qualitative and comparing the result with the PIP evaluation success criteria. The results show that the overall PIP implementation runs well with details in aspects: (a) context, the PIP socialization is implemented well, the PIP objectives performance is in the very good category and can ease students’ costs in the excellent category; (b) input, the school provides particular staffs executing PIP showing the excellent category; (c) process, the targeted accuracy of most PIP students at SMK states that they follow the provisions. Based on the PIP SMK management role and function, the institute has served well; (d) product, most issues reported of the PIP funds for SMK indicate that the use of the fund by students is suitable with the provision and its management. The current model of the PIP aid funds needs to be advanced, particularly with several aspects unsteady.